The Pedagogical Competence Skills of Biology Teacher Candidates - Kukuh Munandar; Muslimin Ibrahim; Leny Yuanita (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The research on "Pedagogical Competence Skills of Biology Teacher Candidates" aims to identify the pedagogical competence profile of biology teacher candidates in biology learning to prepare them in this 21st century. The results of the research are used as: 1) suggestion for stakeholders to improve pedagogical competence of biology teacher candidates, 2) reflection of learning in the department of Biology Education, and 3) recommendation for further research in the development and empowerment of prospective teachers, especially biology teacher. To achieve these goals, this research uses qualitative research method with quantitative descriptive analysis. The data collection instruments are: 1) pedagogical self-evaluation questionnaire, 2) assessment sheets of learning device, 3) assessment sheets of teaching learning process, and 4) teachers’ self-confidence assessment sheets. Based on the data analysis, it can be concluded that the category of pedagogical ability of the students of biology teacher candidates in the assessment is very good (= 3.77 scale 4). Meanwhile, the category of the self-evaluation assessment of prospective biology teacher students is good (= 3.87 scale 5). However, the category of the use of ICT-based learning media is enough  (= 2.2 scale 5).